Colour evolution of conventionally and organically cultivated hungarina red spice paprika varieties - Koncsek A.; Horváth Zs. H.; Véha Antal; Daood H. G.; Helyes L. (2016)
Colour evolution of conventionally and organically cultivated Szegedi-20, Meteorit, Mihálytelki and Kármin spice paprika varieties was studied in green, break, pale red, deep red and over-ripened maturity stages. As the ripening stages forwarded the organic samples gradually lost their initial extractable colour (ASTA value) gain toward their conventional counterparts. The over-ripened colour levels were satisfactorily high in the conventional (169.9-264.8 ASTA) and in the organic (160.8-210.5 ASTA) paprika varieties as well, although the colour accumulation was 9.0- 62.8 ASTA lower in the organic samples. Significant and perceptible visual colour differences (ΔE*ab) were found between the organic and conventional crops. The lightness difference (ΔL*) indicated that the organic paprika generally were lighter than the conventional ones. The positive hue difference (ΔH*ab) showed that the colour of deep red and over-ripened organic Szegedi-20, Mihálytelki and Kármin paprika crops were more yellow compared with the conventional group. The lightness (L*) and hue angle (h°ab) were found the most suitable instrumental colour parameters to distinguish the ripening stages and the colour characteristics of the samples. The better colour evolution of conventional crops was attributed to the soil characteristics, nutrient supply and chemical plant protection that were specifically designed for the needs of paprika in the conventional farming.